2001
DOI: 10.1080/095466301317085363
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the combined effect of cryotherapy and corticosteroid injections versus corticosteroids and cryotherapy alone on keloids: a controlled study

Abstract: Combined injection of intralesional steroids with cryotherapy appears to be superior to other current modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 8 publications
1
19
2
Order By: Relevance
“…No data on reduction in scar size or overall scar improvement could be extracted from the studies of Layton et al (17), Sproat et al (18), and Kelemen et al (19). Finally, eight studies were included in this meta-analysis (11, 16, 2025). The characteristics of these eight studies were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No data on reduction in scar size or overall scar improvement could be extracted from the studies of Layton et al (17), Sproat et al (18), and Kelemen et al (19). Finally, eight studies were included in this meta-analysis (11, 16, 2025). The characteristics of these eight studies were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Since the studies of Yosipovitch et al (20) and Tan et al (11) were not RCT, they were judged as high risk for random sequence generation. Four studies (2225) provided the method used to generate random sequence and were judged to be at low risk of random sequence generation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations